2006
DOI: 10.1124/jpet.106.107987
|View full text |Cite
|
Sign up to set email alerts
|

Ligands Regulate Cell Surface Level of the Human κ Opioid Receptor by Activation-Induced Down-Regulation and Pharmacological Chaperone-Mediated Enhancement: Differential Effects of Nonpeptide and Peptide Agonists

Abstract: Two peptide agonists, eight nonpeptide agonists, and five nonpeptide antagonists were evaluated for their capacity to regulate FLAG (DYKDDDDK)-tagged human opioid receptors (hKORs) stably expressed in Chinese hamster ovary cells after incubation for 4 h with a ligand at a concentration ϳ1000-fold of its EC 50 (agonist) or K i (antagonist) value. Dynorphins A and B decreased the fully glycosylated mature form (55-kDa) of FLAG-hKOR by 70%, whereas nonpeptide full agonists [2-(3,4-dichlorophenyl 17-cyclopropylmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 44 publications
5
30
0
Order By: Relevance
“…rKOR up-regulation was associated with a decrease in the level of the 42-kDa precursor and a concomitant increase in the mature 52-kDa receptor, and the increase in immunoreactivity occurred in parallel with the increase in B max . The 3-to 4-fold up-regulation observed herein was significantly greater than the maximal 30% up-regulation of the human KOR induced by naloxone (Chen et al, 2006). The reason for the discrepant magnitudes of up-regulation may be due to species differences or to the use of different cell lines to express the receptors.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…rKOR up-regulation was associated with a decrease in the level of the 42-kDa precursor and a concomitant increase in the mature 52-kDa receptor, and the increase in immunoreactivity occurred in parallel with the increase in B max . The 3-to 4-fold up-regulation observed herein was significantly greater than the maximal 30% up-regulation of the human KOR induced by naloxone (Chen et al, 2006). The reason for the discrepant magnitudes of up-regulation may be due to species differences or to the use of different cell lines to express the receptors.…”
Section: Discussionmentioning
confidence: 52%
“…1B). After incubation of the cells for 6 h with BFA alone (at a concentration slightly lower than that used previously by Petaja-Repo et al, 2002 andChen et al, 2006), the pattern of rKOR immunoreactivity was altered. After BFA treatment, the predominant receptor species in rKOR cells was a diffuse band with an apparent molecular mass of approximately 44 kDa, and a faint 48-kDa form was also present (Fig.…”
Section: Ligand-induced Up-regulation Of the -Opioid Receptor 617mentioning
confidence: 96%
See 1 more Smart Citation
“…We have shown previously that non-peptide κ full agonists have different efficacies in regulating the hKOR. While U50,488H causes robust phosphorylation, internalization and down-regulation, etorphine does not (Chen et al, 2006b;Li et al, 2000;Li et al, 1999;Li et al, 2003). In the present study, using CHO cells stably expressing the hKOR as the model system, we found that three major dynorphins, Dyn A, Dyn B and α-Neo, induced differential regulation of the hKOR after receptor activation.…”
Section: Introductionmentioning
confidence: 50%
“…We have previously demonstrated that non-peptide agonists down-regulated cell surface FLAG-hKOR to less extents than peptide agonists (Chen et al, 2006b). In addition to causing agonist-induced receptor degradation, non-peptide agonists function intracellularly as pharmacological chaperones to enhance cell surface receptor expression.…”
Section: Agonist-dependent Receptor Adaptation Following Activationmentioning
confidence: 99%